Mechanical behavior of multilayered sandwich panels of wood veneer and a core of cork agglomerates - Lakreb, Nadia; Bezzazi, Boudjema; Pereira, Helena (Materials & Design, 2015)
Sandwich panels were produced using wood veneer of Aleppo pine as face sheets and cork agglomerate as core, including multilayered designs, for use in construction. The mechanical behavior of the panels was tested for perpendicular compression and tensile, longitudinal compression, three and four point bending, and shear. The load–displacement curves, patterns and cracking fractures were analyzed. The cork agglomerate provided a high performance under perpendicular compression, while the wood layers protected the core material and increased mechanical strength under tensile loads. Failure occurred mostly by fracture between cork granules. Multilayered sandwich panels showed higher strength and an increased number of layers improved the mechanical performance of the composite structure. The results suggested that these sandwich panels may be used as construction materials for paneling or partition walls in interior applications with the advantage of environmental friendliness and cost effectiveness.
Keywords: Aleppo pine; Bending; Compression Tension; CORK AGGLOMERATES; sandwich multilayer panels

Influence of raw-material quality and process parameters in the production of insulation cork agglomerates - Pereira, H; Baptista, C (European Journal of Wood and Wood Products, 1993)
{Insulation cork agglomerates are produced with different low-cost raw-materials unsuitable for other products: virgin corks (from prunmgs, thinnings anti dead trees), reproduction corks (refuse and underaged) and industrial byproducts (corkback strips). These materials were analysed in relation to chemical composition, struc- ture and trituration behaviour. The industrial byproducts diffcr significantly from the other materials due to the presence of an important amount of the unsubcriscd lignocellulosic phlocm (the back of the corkboards) in a way that is detrimental to the agglomeration process. The influence of raw-material, granulometry and process parameters (time, temperature and pressure} were studied using an experimental autoclave. Temperature is the deter- mining factor for agglomeration. Insufficient adhesion is obtained under 230 ~C and adequate agglomeration is attained only with temperatures in the range 230 300 "C. corresponding to inass losses of 10 25%.
Keywords: chemical composition; CORK AGGLOMERATES; Raw materials; structure; trituration behaviour (Voyant)

Influence of raw-material quality and process parameters in the production of insulation cork agglomerates - Pereira, H.; Baptista, C. (European Journal of Wood and Wood Products, 1993)
{Insulation cork agglomerates are produced with different low-cost raw-materials unsuitable for other products: virgin corks (from prunmgs, thinnings anti dead trees), reproduction corks (refuse and underaged) and industrial byproducts (corkback strips). These materials were analysed in relation to chemical composition, struc- ture and trituration behaviour. The industrial byproducts diffcr significantly from the other materials due to the presence of an important amount of the unsubcriscd lignocellulosic phlocm (the back of the corkboards) in a way that is detrimental to the agglomeration process. The influence of raw-material, granulometry and process parameters (time, temperature and pressure} were studied using an experimental autoclave. Temperature is the deter- mining factor for agglomeration. Insufficient adhesion is obtained under 230 ~C and adequate agglomeration is attained only with temperatures in the range 230 300 "C. corresponding to inass losses of 10 25%.
Keywords: chemical composition; CORK AGGLOMERATES; Raw materials; structure; trituration behaviour (Voyant)

WETTING OF CORK BY POLYMERIC ADHESIVES - ADAO, M H; CABRITA, G M; GOMES, C M; ALMEIDA, B S; FERNANDEZ, A C; Bordado, J C (JOURNAL OF ADHESION SCIENCE AND TECHNOLOGY, 1993)
The cohesion of cork agglomerates is determined by the strength of the adhesive joint established between the polymeric adhesive and the cork particles. The ability of adhesives to form good joints depends, among other factors, on the wetting of cork by the adhesives. The main objective of this research was to study the behaviour of adhesive drops deposited on cork substrates through measurements of contact angles and their time dependence. Several polyurethane prepolymers were tested to establish a correlation between the wetting characteristics and the chemical structure and physical properties of the adhesives. The effect of the morphology of cork on the interfacial properties was also investigated. The initial contact angles were related to the chemical nature of the adhesive. The kinetics of the wetting process were found to depend mainly on the viscosity of the adhesive.
Keywords: CONTACT ANGLE; CORK AGGLOMERATES; POLYMERIC ADHESIVES; WETTING